(untitled) - The World Bank in VietNam (WB) (Ha Noi, 2003)
The project provided satisfactory results for Vietnam. A substantial debt reduction was effected and debt obligations were regularized, favoring a sustainable balance of payments and state budget. However, secondary market prices have fallen, reflecting both the external environment due to the Asian financial crisis, and perceived weakened prospects for Vietnam. The key lessons learned show that the immediate objective of reducing external obligations was achieved in an overall strategy on external debt management. The grant from the Debt Reduction Facility provided legal and financial assistance for mastering the intricacies of international finances and debt restructuring activities, allowing a smooth implementation of the project. The effective cooperation and coordination between the Government and the Bank, gave way to successful preparation, appraisal, and implementation of the project. Nevertheless, experience suggests that a successful debt rescheduling can only be achieved within the context of a viable structural reform program. Further external debt strategies are required, namely, the negotiation of the debt rescheduling package with the Russian Federation, and the coordination of an external debt management for sustainable creditworthiness, servicing external obligations.
Keywords: Debt,Nợ; Reduction,Giảm